Incorporation of N0 stage with insufficient numbers of lymph nodes into N1 stage in the seventh edition of the TNM classification improves prediction of prognosis in gastric cancer—results of a single-institution study of 1 258 Chinese patients - Bo-Fei Li; Zhi-Wei Zhou (临床与病理杂志; 卷 35, 编号 1 (6 2015), 2026)
Objective: This study examined the prognosis of the “node-negative with eLNs ≤15” designation and the additional value of incorporating it into the pN1 designation in the seventh edition N classification. Methods: From Jan 2000 to Sep 2010, a total of 1,258 gastric cancer patients undergoing radical gastric resection were enrolled. We incorporated node-negative patients with eLNs ≤15 into pN1 and compared this designation with the 7th edition UICC N stage for 3.5- year overall survival by univariate and multivariate analysis. Homogeneity, discriminatory ability, and monotonicity of gradients in hypothetical N stage and UICC N stage were compared using linear trend χ2, likelihood ratio χ2 statistics, and Akaike information criterion (AIC) calculations. Results: Node-negative patients with eLNs ≤15 had worse survival compared with those with eLNs >15. The hypothetical N stage had higher linear trend and likelihood ratio χ2 scores and smaller AIC values compared with those for the 7th edition N stage, which represented the optimum prognostic stratification. Conclusion: Nodenegative patients with eLNs ≤15 can be considered to be incorporated into the pN1 stage in the 7th edition of th e TNM classification.